EFFICIENCY OF STABILIZING OF FOOD FATS AND POSSIBILITY OF EXTENDING THEIR STORAGE TERMS - CHUIKO, MARYNA; CHUIKO, ANDRII (Herald of Khmelnytskyi National University. Technical sciences, 2022)
It is important today to increase the shelf life of fats used for the production of culinary and confectionery products in the food industry and in the restaurant industry. Fats are part of a variety of dishes and products in various quantities (from 1 % in fresh salads to almost 85 % in creams). When stored under the influence of light, air and moisture in fats, chemical reactions occur, mainly oxidative, which significantly impair their organoleptic and physicochemical parameters. In existing recipes, most dishes use mainly vegetable oil, margarine, cooking fat, and for children's and special dietary foods - butter. Therefore, it was important to investigate the use of powders from different fractions of grape pomace and pomace extract as antioxidants for some fats with a very limited shelf life, including butter and margarine, which are often used to produce a variety of culinary products and confectionery. The article is devoted to topical issues of using powders from different fractions of grape pomace and their extract as antioxidants for food fats. A previous analysis of the chemical composition of powders from grape pomace showed that they retain as much as possible in native form all biologically active substances and vitamin complexes, including those responsible for antioxidant activity. It is established that to slow down the oxidation of fats and increase their shelf life, it is rational to pre-introduce into these fats powders of grape pomace in the amount of 5 % by weight of fat and extract from grape pomace in the amount of 0,5 % (dry matter) by weight fat. Such concentrations of additives do not impair the organoleptic and physicochemical parameters of the quality of the original product and can extend the shelf life, in particular, butter by 30-80 %. Such an increase in the shelf life of butter in production will contribute to a slower accumulation of free acids and peroxides during the established shelf life.
Keywords: fats; fat stabilization; grape pomace powders; antioxidants; fat storage; fat oxidation; butter; margarine